2006
DOI: 10.1364/ao.45.001583
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion characterization of durable silver coatings by electrochemical impedance spectroscopy and accelerated environmental testing

Abstract: Highly reflective front-surface silver mirrors are needed for many optical applications. While various protective dielectric coating schemes have been developed, the long-term durability of Ag mirrors is still of great concern in the optics community for a variety of applications under harsh environments. The corrosion protection behavior of a SiNx-coated silver-mirror coating scheme was tested with electrochemical impedance spectroscopy (EIS) and accelerated environmental testing, including humidity and salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Therefore, in a first approach, the interface between the silver/Si 3 N 4 /electrolyte can be represented by the classical equivalent circuit shown in Figure 7 proposed for the first time in reference26 and used in references. [18][19][20][21][22] The impedance corresponding to the proposed model ( Figure 7) can be written as…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in a first approach, the interface between the silver/Si 3 N 4 /electrolyte can be represented by the classical equivalent circuit shown in Figure 7 proposed for the first time in reference26 and used in references. [18][19][20][21][22] The impedance corresponding to the proposed model ( Figure 7) can be written as…”
Section: Results and Analysismentioning
confidence: 99%
“…They used an equivalent circuit that took into account both open and closed pores. Tse Chu et al 22 showed that dielectric protected silver reflectors can be reasonably described by an equivalent circuit consisting of two constant phase element (CPE) components. They considered only the modulus of the impedance to characterize the electrochemical behavior of the dielectric film.…”
mentioning
confidence: 99%
“…There are numerous approaches to developing protected silver coatings which combine an effective protection of the silver film with good optical properties. Several investigations of the durability of protected silver have already been published [4,5,[7][8][9][10]. The most investigated coatings are based on the patented coating design from Wolf et al [6].…”
Section: B Investigation Of a Defect Mechanism In Protected Silver Cmentioning
confidence: 99%
“…the Gemini twins or the Kepler Space Telescope [4,5], are using mirrors with this kind of coating. However, even though protected silver coatings were extensively studied and optimized in the recent years, the appearance of defects after extensive exposure of protected silver mirrors to humid atmosphere remains still an important topic [7].…”
Section: B Investigation Of a Defect Mechanism In Protected Silver Cmentioning
confidence: 99%
“…However, NiCr nitride has very poor transmission in the optical wavelengths; as a consequence, the upper layer must be exceedingly thin. Chu et al 7 report that as little as 3 Å (ie. just 1-2 atomic thicknesses!)…”
Section: Silver: the Gemini/llnl Style Coatingmentioning
confidence: 99%